Inside the teaching machine : rhetoric and the globalization of the U.S. public research university - Chaput, Catherine (Rhetoric, culture, and social critique., 2008)
Focuses on the relationship between American universities and globalization, showing how the trend toward professionalization contributes to the production of surplus value and the ways that the American university model circulates outside the United States.